Autoimmune-like drug-induced liver injury: a review and update for the clinician. (1st November 2016) - Stine, Jonathan G.; Northup, Patrick G.
ABSTRACT: Introduction : Autoimmune-like drug-induced liver injury (DI-AIH) is a rare but serious event with a growing body of scientific evidence and a fair degree of uncertainty. Areas covered : This review covers the definition, pathophysiology, treatment and patient-centered outcomes of DI-AIH and presents up-to-date information on the most commonly implicated drugs. Expert opinion : A high degree of clinical suspicion is required for the diagnosis of DI-AIH. This diagnosis should be considered in any patient with either acute or chronic elevations in liver-associated enzymes. Prevalence rates exceed 15% based on large international registry data. Autoantibodies, while common, are neither specific nor diagnostic of DI-AIH. Histology may be helpful in describing subtle differences between DI-AIH and de novo idiopathic autoimmune hepatitis (iAIH), but oftentimes the two are indistinguishable histologically. Alpha-methyldopa, fibrates, hydralazine, minocycline, nitrofurantoin, HMG-CoA reductase inhibitors (statins), iplimumab and tumor necrosis factor alpha antagonists are the most commonly associated drugs with DI-AIH. Complete recovery of liver injury is most often seen with DI-AIH, however, cases of prolonged injury may occur and may require treatment with immunosuppressive therapy. Relapse following cessation of corticosteroids for suspected DI-AIH should prompt reconsideration of the diagnosis and further exploration into possible iAIH.